2022
DOI: 10.1007/s12325-022-02387-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Direct Oral Anticoagulants Among Patients with Non-valvular Atrial Fibrillation and Multimorbidity

Abstract: Introduction: In the USA, there is a steady rise of atrial fibrillation due to the aging population with increased morbidity. This study evaluated the risk of stroke/systemic embolism (S/SE) and major bleeding (MB) among elderly patients with non-valvular atrial fibrillation (NVAF) and multimorbidity prescribed direct oral anticoagulants (DOACs). Methods: Using the CMS Medicare database, a retrospective observational study of adult patients with NVAF and multimorbidity who initiated apixaban, dabigatran, or ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The original randomized ROCKET AF trial 3 , 4 and ARISTOTLE 7 trial had median follow-ups of 1.6 and 1.8 years, respectively. In many of the recent observational studies we reviewed, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 many had follow-up durations of only 3 to 6 months. All major outcomes in ROCKET AF trial 3 , 4 and ARISTOTLE 7 vs vitamin K antagonists were adjudicated by committee members who were blinded to treatment allocation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original randomized ROCKET AF trial 3 , 4 and ARISTOTLE 7 trial had median follow-ups of 1.6 and 1.8 years, respectively. In many of the recent observational studies we reviewed, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 many had follow-up durations of only 3 to 6 months. All major outcomes in ROCKET AF trial 3 , 4 and ARISTOTLE 7 vs vitamin K antagonists were adjudicated by committee members who were blinded to treatment allocation.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 339 studies were initially identified of which 230 studies were excluded based on the exclusion criteria. On review of the remaining 109 studies, full texts were reviewed, and 41 studies were included for final review 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ( Figure 1 ). Not all studies reviewed are referenced further.…”
Section: Methodsmentioning
confidence: 99%
“… 338 On the contrary, in two very large claim-based and propensity score-matched analyses exploring the interaction between NOACs, VKAs, and multi-morbidity, all data strongly underline how apixaban seems to have a better effectiveness and safety profile compared to warfarin, dabigatran, and rivaroxaban in multi-morbid AF patients. 339 , 340 …”
Section: Special Circumstances With Regards To Stroke Prevention In A...mentioning
confidence: 99%
“…This result is even more concerning since exposure outside of on-therapy ranges is known to be related to stroke and bleeding events. Nevertheless, real-life clinical data support the safety of dabigatran even in high-risk groups ( 32 , 33 ), which is further increased by the availability of its specific antidote idarucizumab.…”
Section: Introductionmentioning
confidence: 99%